Transforming Technology: A Critical Theory Revisited - Feenberg, Andrew (Oxford University Press, 2002)
Thoroughly revised, this new edition of Critical Theory of Technology rethinks the relationships between technology, rationality, and democracy, arguing that the degradation of labor–as well as of many environmental, educational, and political systems–is rooted in the social values that preside over technological development. It contains materials on political theory, but the emphasis has shifted to reflect a growing interest in the fields of technology and cultural studies.
Google-Books-ID: eInpwEpC_HgC
Keywords: Political Science / History & Theory; Political Science / Public Policy / Social Services & Welfare